«To supplement the characteristics of the domestic and foreign policy of the Kolchak government in Siberia»: an urgent secret letter from Siberian revolutionary committee to the people’s commissar G. V. Chicherin (April 9, 1924) - D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The publication introduces into the scientific circulation previously unknown sources about the foreign policy and financial and economic activities of the anti-Bolshevik authorities in the East of Russia in 1918–1920, as well as about departmental storage of documents in the financial authorities of Siberia during the first years of Soviets. The work is addressed to specialists studying international relations, financial policy and archiving during the Civil War and the first years after its end